2022
DOI: 10.36923/jicc.v22i2.35
|View full text |Cite
|
Sign up to set email alerts
|

International career aspirations: Can multicultural personality traits predict the interest in working abroad?

Abstract: The business world is faced with the need to create new strategies in order to identify a global mentality and an international motivation in professionals who hardly work anymore in monocultural environments. This study investigates the characteristics of international career aspirations to identify multicultural personality traits that may predict interest in working abroad. Empirical research has been carried out with 243 individuals using the Multicultural Personality Questionnaire (MPQ), a multidimensiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…These strategies are best used for simple tasks and activation of information in working memory (Pintrich, Smith, Garcia & Mckeachie, 1995). The second type assesses deep cognitive engagement, which is considered to help students store information in long-term memory by building internal connections between items to be learned (Pintrich et al 1995;Carballal-Broome & Pinillos, 2022). Elaboration strategies include paraphrasing, summarizing, creating analogies, and generative notetaking.…”
Section: Cognitive Learning Strategiesmentioning
confidence: 99%
“…These strategies are best used for simple tasks and activation of information in working memory (Pintrich, Smith, Garcia & Mckeachie, 1995). The second type assesses deep cognitive engagement, which is considered to help students store information in long-term memory by building internal connections between items to be learned (Pintrich et al 1995;Carballal-Broome & Pinillos, 2022). Elaboration strategies include paraphrasing, summarizing, creating analogies, and generative notetaking.…”
Section: Cognitive Learning Strategiesmentioning
confidence: 99%
“…Numerous empirical studies testing this theory revealed that cultural value, self-construal, relational and situational factors, emotions, interpersonal transgressions and forgiveness, intergenerational face, and the dark side of the face were important factors in people's preference of conflict styles across cultures (Cai and Fink 2002;Ting-Toomey et al 1991;Trubisky, Ting-Toomey, and Lin 1991;Oetzel and Ting-Toomey 2003;Baig, Ting-Toomey, and Dorjee 2014;Dorjee, Baig, and Ting-Toomey 2013;Zhang et al 2019;Carballal-Broome & Pinillos, 2022).…”
Section: Face-negotiation Theory (Fnt)mentioning
confidence: 99%